The Effectiveness of Combining Mind’s Eye and Story Impression Strategies in Teaching Reading Comprehension in Second Year Students - Wiratno Wiratno; M. Alimul Huda (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2024)
The clarification of this investigate is depended in factual examination that utilized SPSS with utilized ANCOVA for analyzed procedure. This study can conclude as follows. The result from the yield of ANCOVA may for replied the address which be an issue in this consider. The result appeared centrality esteem uniformity of change more than 0.005 that was 0.076. That was the table test between subject impact appeared centrality esteem littler than 0.005 that was 0,000 from the result of centrality esteem there was contrast between the understudies who instructed utilized combining mind's eye and story impression methodologies with the understudies instructed utilized GTM. From the result over so, combining mind's eye and story impression procedures is more successful than GTM.